An Intervention Framework for Addressing Stigma on College Campuses: Findings From a 3-Year-Long Intervention Program. Issue 9 (29th March 2022) - Tomar, Nikhil; Jensen, Todd M.; Pace, Nelson
Abstract: The ongoing COVID-19 pandemic will only exacerbate the rising mental health concerns among college students. However, stigma toward such concerns continues to hinder mental health care utilization among the students, requiring urgent evidence that can help guide college campuses in implementing effective antistigma interventions. We propose and provide evidence for an intervention based on findings from a 3-year-long antistigma intervention that was implemented on a Southeastern college campus in the United States. Unique random samples of college students, totaling N = 1727 across 3 years, were recruited as participants. Each year, participants completed a preintervention and postintervention survey comprising of questions related to demographics, stigma, and mental health care knowledge. Findings indicate that the stakeholder-led intervention decreased personal stigma and increased mental health care knowledge among students who were exposed to the intervention. Further research is needed to assess feasibility and efficacy of the proposed intervention framework on other campuses.